GDP Per Capita Versus Median Household Income: What Gives Rise to Divergence Over Time? - Brian Nolan; Max Roser; Stefan Thewissen (Luxembourg Income Study (LIS), 2016)
Divergence between the evolution of GDP per capita and the income of a 'typical' household as measured in household surveys is giving rise to a range of serious concerns, especially in the USA. This paper investigates the extent of that divergence and the factors that contribute to it across 27 OECD countries, using data from OECD National Accounts and the Luxembourg Income Study. While GDP per capita has risen faster than median household income in most of these countries over the period these data cover, the size of that divergence varied very substantially, with the USA a clear outlier. The paper distinguishes a number of factors contributing to such a divergence, and finds wide variation across countries in the impact of the various factors. Further, both the extent of that divergence and the role of the various contributory factors vary widely over time for most of the countries studied. These findings have serious implications for the monitoring and assessment of changes in household incomes and living standards over time.
Keywords: 330; Economic growth; inequality; household incomes